PENINGKATAN SARANA DAN METODE PEMBELAJARAN AL-QUR’AN DI TPQ AL-WARDAH DESA WANAR KABUPATEN LAMONGAN - Abdulloh Hanif; Risma Firda Diana (LPPM Universitas Islam Darul 'Ulum Lamongan, 2023)
TPQ Al-Wardah is the first TPQ in Wanar Village which until now has less than 100 students fostered by 6 Asatidzah. The method used at TPQ Al-Wardah is the An-Nahdiyah method. Based on the results of the Focus Group Discussion (FGD), the formulation of the problem tree, and the formulation of the hope tree, it shows that TPQ Al-Wardah Desa Wanar still needs guidance, especially in the field of procurement and management of infrastructure that can support better educational institutions. In addition, the method of teaching the Koran at TPQ Al-Wardah is still monotonous, making it boring and less effective. Institutional strengthening through empowering educational resources at TPQ Al-Wardah needs to be done before maximizing other elements. Therefore, community service activities were carried out at TPQ Al-Wardah entitled upgrading or improving Al-Qur'an learning facilities and methods. The strategies used in this activity were (1) conducting FGDs with related institutions and agencies, (2) formulating various learning methods and infrastructure needed by TPQ Al-Wardah, (3) updating recitation infrastructure at TPQ Al Wardah, ( 4) organize training on fun Al-Quran learning methods through the 3B method (Playing, Storytelling, and Singing) as well as practical learning methods. The facilities provided in this activity were bookcases, Al-Qur'an, several volumes of An-Nahdliyah books, stationery, and visual aids. In addition, in this activity training was held on the Al-Qur'an 3B learning method (Playing, Learning, and Storytelling) for teachers.